2005
DOI: 10.1016/j.matlet.2005.01.043
|View full text |Cite
|
Sign up to set email alerts
|

CVD growth of carbon nanotubes directly on nickel substrate

Abstract: Chemical vapor deposition (CVD) growth of carbon nanotubes directly on nickel substrates was carried out at different temperatures. Effects of temperature on the growth of carbon nanotubes were investigated and the nucleation and growth mechanism of carbon nanotubes at different temperature ranges were also discussed. Based on the growth mechanism of nanotubes, small amount of Fe nanoparticles were deposited on the nickel substrate to introduce more nucleation sites at elevated temperature, and the density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…It has been previously reported that the grain boundaries on bulk metals act as nucleation sites [3,47] due to change in local topography and/or effect of local impurities [69]. Also, grain boundaries provide a fast path for mass transport [39]. The enhanced mass transport into faceted nickel foil accelerated the formation of crystallites, which resulted in the increase in carbon yield.…”
Section: Mechanism Of Cnf Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that the grain boundaries on bulk metals act as nucleation sites [3,47] due to change in local topography and/or effect of local impurities [69]. Also, grain boundaries provide a fast path for mass transport [39]. The enhanced mass transport into faceted nickel foil accelerated the formation of crystallites, which resulted in the increase in carbon yield.…”
Section: Mechanism Of Cnf Synthesismentioning
confidence: 99%
“…However, CNF/CNT synthesis on bulk metal substrates is challenging because the exact dimensions of the catalyst cannot be controlled, and as a result high levels of amorphous carbon may be formed. Several investigators have reported synthesis of CNF/CNT on bulk stainless steel substrates [30][31][32][33][34][35]; however, there are relatively few reports of CNF synthesis on bulk nickel metal substrates such as foams [36][37][38], screens/grids [39], and foils [40][41][42][43]. Pretreatment of the bulk metal has been studied for its effects on CNF/CNT growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that Ni can be used as a catalyst for the growth of CNTs. [8,19,32] Furthermore, Du and Pan [32] grew multiwalled CNTs by directly using Ni grids as catalytic active substrates. When analyzing the samples obtained with both approaches, it was observed that many of the SWCNTs had one of their ends on the Ni metal grid (Fig.…”
Section: Synthesis Of Cnts Directly From the Ni Grid: Control Experimmentioning
confidence: 99%
“…The most frequently used catalysts are transition metals, the primary catalyst of iron (Fe) [9], cobalt (Co) [9,10], nickel (Ni) [11,12] or dual transition metal Fe-Co on supporting material such zeolite [13]. In the case of the abundance and simplicity to obtain the catalyst, Fe catalyst can be a good choice because its uses in CVD method would produce higher yield compared to Co catalyst uses in producing CNT.…”
Section: Introductionmentioning
confidence: 99%